Analysis of Indonesian Port Integration System Performance (Inaportnet) Based On Pieces Framework Variables In 2021 - Sekarwati Ariadi, Tiara; Malisan, Johny; Sugiharti, Endang (Green Publisher Indonesia, 2022)
This study is aimed at identifying the variables of the Indonesian Port Integration (Inaportnet) System Performance Based on the Piece Framework Variables in 2021. The built model includes explanations. Six independent variables (independent) and one dependent variable (dependent). Variables that have positions as independent variables are performance, information and data, economy, control and security, efficiency, and service. The variable that acts as a variable is user satisfaction. Data analysis was performed using the Multiple Linear Regression Analysis approach. The data used are primary, quantitative, and cross-sectional data. The data were collected from 80 respondents by distributing questionnaires using a Likert scale with five answer choices. Data analysis was carried out with the help of the SPSS application. The results of testing variables, namely performance, and economics, show that there is a significant influence on the user satisfaction variable, while for the variables, information and data, control and security, efficiency, and service do not have a significant effect on the user satisfaction variable, it is evident from the results of the T test where the performance variable, and economics showed a significant level less than 0.05, and was positive for user satisfaction, and the information and data, control and security, efficiency, and service showed variables a significant level greater than 0.05 , and declared no positive effect on user satisfaction